Simultaneous observations of MHD hot flow anomaly and kinetic foreshock bubble and their impacts - Lu, Xi; Liu, Terry; Chen, Xingran; Otto, Antonius; Zhang, Hui (Frontiers in Physics, 2025)
Hot flow anomalies (HFAs) and foreshock bubbles (FBs) are two types of transient phenomena characterized by flow deflected and hot cores bounded by one or two compressional boundaries in the foreshock. Using conjunction observations by the Time History of Events and Macroscale Interactions during Substorms (THEMIS) mission, we present an MHD HFA with a core filled with magnetosheath material around the bow shock and a typical kinetic FB associated with foreshock ions upstream of the bow shock, occurring simultaneously under the same solar wind/interplanetary magnetic field (IMF) conditions. The displacements of the bow shock moving back and forth along the sun-earth line are observed. Electron energy shows enhancements from ∼50 keV in the FB to ∼100 keV in the HFA core, suggesting additional acceleration process across the bow shock within the transient structure. The magnetosheath response of an HFA core-like structure with particle heating and electron acceleration is observed by the Magnetospheric Multiscale (MMS) mission. Ultralow frequency waves in the magnetosphere modulating cold ion energy are identified by THEMIS, driven by these transient structures. Our study improves our understanding of foreshock transients and suggests that single spacecraft observations are insufficient to reveal the whole picture of foreshock transients, leading to an underestimation of their impacts (e.g., particle acceleration energy and spatial scale of disturbances).